Enteral feeding protocol: a quality improvement project on feeding interruptions and clinical outcomes in a tertiary intensive care unit - Ng, Boon Hui; Wan Mat, Wan Rahiza; Teo, Rufinah; Izaham, Azarinah; Abd Kader, Mohd Khazrul Nizar; Md Zain, Jaafar; Mohamad Mahdi, Siti Nidzwani; Musthafa, Qurratu Aini; Mohamad Yusof, Aliza (Frontiers in Medicine, 2025)
PurposeEvaluation of the effectiveness of the feeding protocol in improving feeding interruption (FI) and clinical outcome in critically ill patients.Materials and methodsThis was a single-center, retrospective, and prospective cohort study design evaluating the nutritional characteristics and adequacy, and the causes and clinical outcomes of FI, pre- and post-feeding protocol implementation. The risk factor for ICU mortality was also identified.ResultsIn total, 430 patients were included, 217 in the pre-protocol group and 213 in the post-protocol group. After protocol implementation, energy and protein intake significantly improved, and the total target nutrition was achieved. The post-protocol group was prescribed a more energy-dense formula (29.0% vs. 55.4%, p < 0.001), a protein supplement (27.6% vs. 56.3%, p < 0.001), and a prokinetic agent (38.7% vs. 48.8%, p = 0.03). There was no difference in the duration of feeding interruption (28 h vs. 30 h, p = 0.60). Implementation of feeding protocol did not affect ICU mortality (OR 0.508, CI 0.250–1.032, p = 0.06). The mortality predictors were SOFA score, underweight, and illness-related FI episode.ConclusionImplementation of the feeding protocol improved feeding strategies and overall nutritional intake; however, it did not improve FI. Illness-related FI was associated with a reduction in survival of critically ill patients.